Effect of GANIME form and it’s efficacy on Lee index and albumin levels in rats with energy-protein deficiency (PED) - Sanjaya, Dandi; Indarto, Dono; Nurwati, Ida; Iwansyah, Ade Chandra (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
ABSTRACTBackground: The prevalence of Protein Energy Deficiency (PED) has increased over the past decade. Inadequate food intake and infectious diseases are the primary causes of PED. Clinical management of toddlers with PED often involves costly commercial foods. Ganyong, catfish, and red beans as local food ingredients with high nutritional content have the potential to be additional food for children with PED.Objectives: This study aims to examine the effect of GANIME formula form and it’s efficacy on body mass index (BMI) and albumin levels in the rats model with PED.Methods: The study consisted of two phases: analyzing the proximate content of GANIME and conducting in vivo research using ten male Wistar rats aged 3 weeks (50-100 grams). The rats were randomly divided into two groups, G1 (GANIME pellets) and G2 (GANIME porridge), and were observed for 14 days. Body weight (BW), BMI, and albumin were measured before and after treatment. Paired t-tests were conducted to compare pre-and post-treatment results, while inter-group differences were assessed using One-Way Analysis of Variance (ANOVA) tests.Results: The results showed that the optimal GANIME formula was identified at P3, with the highest protein and energy  content. The G1 group of rats experienced a greater increase in body weight and BMI than the G2 group of rats but the increase was not significant (p > 0.05). Each group did not differ statistically significantly (0.644). Albumin in each group experienced a non-significant decrease (p > 0.05) and the two were not statistically different (0.690).Conclusions: Administering the GANIME formula in pellet form exhibited superior efficacy because it’s consumed more so it can increase body weight and BMI, and produce a lower decrease in albumin levels in rats model with PED. KEYWORD: protein-energy deficiency (PED), albumin, body mass index (BMI), local food, GANIME formula